PENEGAKAN HUKUM REGISTRASI KARTU PRABAYAR MENGGUNAKAN IDENTITAS ORANG LAIN (Mimbar Keadilan, 2022)
This study discusses the actions of everyone who registers a prepaid card using another person's identity which results in the identity of the prepaid card and prepaid card user being not the same so that this can actually be detrimental to the identity card owner, especially if the prepaid card that has been registered with the identity of another person Otherwise if its use is misused, it is necessary to make efforts to find out the juridical basis and enforce the law on anyone who registers a prepaid card using another person's identity against the law to provide a sense of security to the public regarding the protection of personal data. This study uses a normative juridical research method with a statute approach and a conceptual approach. The results show that law enforcement against anyone who registers a prepaid card using someone else's identity so that the prepaid card has a different identity between the owner of the identity attached to the prepaid card and the user of the prepaid card can actually be enforced by law by being asked for criminal liability and being sued civilly.